2008
DOI: 10.1016/j.ibmb.2007.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Domain organization and phylogenetic analysis of the chitinase-like family of proteins in three species of insects

Abstract: A bioinformatics-based investigation of three insect species with completed genome sequences has revealed that insect chitinase-like proteins (glycosylhydrolase family 18) are encoded by a rather large and diverse group of genes. We identified 16, 16 and 13 putative chitinase-like genes in the genomic databases of the red flour beetle, Tribolium castaneum, the fruit fly, Drosophila melanogaster, and the malaria mosquito, Anopheles gambiae, respectively. Chitinase-like proteins encoded by this gene family were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
160
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(166 citation statements)
references
References 50 publications
5
160
1
Order By: Relevance
“…They differ in their developmental patterns and tissue specificities of expression. Phylogenetic analysis indicates that the appearance of these distinct groups of chitinases predates the separation of coleopteran and lepidopteran lineages of insects (8). Results from RNAi studies reported here support the hypothesis that genes in different groups have distinctly different biological functions.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…They differ in their developmental patterns and tissue specificities of expression. Phylogenetic analysis indicates that the appearance of these distinct groups of chitinases predates the separation of coleopteran and lepidopteran lineages of insects (8). Results from RNAi studies reported here support the hypothesis that genes in different groups have distinctly different biological functions.…”
Section: Discussionsupporting
confidence: 76%
“…Group II chitinases contain at least four catalytic domains and four putative chitin-binding domains, three of which are clustered between two catalytic domains (8). The domain organization of TcCHT10 is similar to that of the T. molitor ortholog, which contains five catalytic domains, of which the first and second were predicted to lack enzymatic activity (6).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Therefore mechanisms that coordinate assembly and maturation of all new cuticles are critical for barrier integrity. Even though production and degradation are well described in insects (1)(2)(3)(4)(5)(6), the regulatory processes of forming compact aECM barriers remain poorly understood.…”
mentioning
confidence: 99%
“…In contrast, two insect chitinase inhibitors, allosamidin [26] and psammaplin A [29], and an oligosaccharide that mimics allosamidin [5] have been shown to induce high mortality rates and reduce fecundity of M. persicae when fed with artificial diet [5,24]. Among all insect chitinase proteins isolated from Lepidoptera [1,[16][17][18], Coleoptera [12,33] and Diptera [7,33,34], only 14 protein sequences are available [31]. Moreover, most investigated chitinases were from Lepidopteran species such as Manduca sexta and Bombyx mori [16], two important economic Lepidopteran pests.…”
Section: Introductionmentioning
confidence: 99%